2010
DOI: 10.1186/1471-2164-11-704
|View full text |Cite
|
Sign up to set email alerts
|

Human transcriptional interactome of chromatin contribute to gene co-expression

Abstract: BackgroundTranscriptional interactome of chromatin is one of the important mechanisms in gene transcription regulation. By chromatin conformation capture and 3D FISH experiments, several chromatin interactions cases among sequence-distant genes or even inter-chromatin genes were reported. However, on genomics level, there is still little evidence to support these mechanisms. Recently based on Hi-C experiment, a genome-wide picture of chromatin interactions in human cells was presented. It provides a useful mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…Intriguingly, these two separate regions, over 2.3Mb apart, interact with each other in T-cells but not B-cells ( S1 Fig ), suggesting that these pathways may converge to give rise to disease-specific MS mechanisms in a stimulus and cell type specific manner. In this regard, it has been previously shown that there is a correlation between chromatin interactions and gene co-expression [3639] and it has been hypothesised that multiple co-regulated genes can interact and share regulatory elements at specialised ‘transcription factories‘ [16]. Our data possibly supports this idea and suggests a possible co-regulation of genes in this region in MS.…”
Section: Resultssupporting
confidence: 85%
“…Intriguingly, these two separate regions, over 2.3Mb apart, interact with each other in T-cells but not B-cells ( S1 Fig ), suggesting that these pathways may converge to give rise to disease-specific MS mechanisms in a stimulus and cell type specific manner. In this regard, it has been previously shown that there is a correlation between chromatin interactions and gene co-expression [3639] and it has been hypothesised that multiple co-regulated genes can interact and share regulatory elements at specialised ‘transcription factories‘ [16]. Our data possibly supports this idea and suggests a possible co-regulation of genes in this region in MS.…”
Section: Resultssupporting
confidence: 85%
“…There is increasing support for PEIs being necessary for transcriptional regulation of an enhancer’s target gene. For example, there is evidence that the expression of a target gene is affected by gain or loss of competing promoters, lack of some PEI-associated proteins and addition of PEI-disrupting insulators [14], as well as evidence that chromatin interactions are highly associated to gene co-expression rates [15]. However, important challenges remain, such as finding the mechanisms that mediate PEIs, the building of high-resolution PEI maps in different cell types and the identification of functional interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Evidences of the 3D genome conformation role in regulating and maintaining cellular functions are continuously emerging (Lieberman-Aiden et al, 2009; Dong et al, 2010; Schoenfelder et al, 2010; Gerstein et al, 2012; Kalhor et al, 2012; Lan et al, 2012; Shen et al, 2012; Homouz and Kudlicki, 2013; Jin et al, 2013; Papantonis and Cook, 2013; Babaei et al, 2015). For example, pathological genome organizations can be associated with many diseases, such as muscular dystrophy (Petrov et al, 2008) and Rett syndrome (Horike et al, 2005).…”
Section: Introductionmentioning
confidence: 99%